REGULASI EMOSI DAN RESILIENSI PADA MAHASISWA TAHUN PERTAMA - Erlina Listyanti Widuri (Universitas Ahmad Dahlan, 2012)
AbstractThis study aims to determine the relationship between emotionregulation and resilience of the first year student at Ahmad Dahlan University. The number of subjects in this research to were 75 students. Pearson product moment correlation was used t analysis the data. The results of this study indicated that there was a significant positive relationship between emotion regulation and resilience.Keywords:college student, emotion regulation, resilienc